2004
DOI: 10.1021/ja048839s
|View full text |Cite
|
Sign up to set email alerts
|

Control of Metal Coordination Number in de Novo Designed Peptides through Subtle Sequence Modifications

Abstract: Substitution of an alanine for leucine (shown in light blue) in the hydrophobic interior of designed three-stranded coiled coils allows for the control of metal ion coordination number and geometry. The influence of this perturbation by a noncoordinating residue can be monitored by the dramatic impact on the 113Cd NMR spectrum. The structural effect occurs even when the residue substitution is as much as 7 A from the metal binding site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
82
1
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 52 publications
(87 citation statements)
references
References 17 publications
2
82
1
2
Order By: Relevance
“…Consequently, the supramolecular arrangement of MBPC-1 *Previous work by several groups has shown that various preexisting folds can be employed as stable scaffolds for hosting diverse metal coordination environments. Some of such engineered metalloproteins manifest properties characteristic of highly evolved natural systems, such as metal selectivity (30), redox tunability (31,32) as well as open coordination sites that allow for reactivity (33) and reversible small molecule binding (34). 1 These authors contributed equally to this work.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the supramolecular arrangement of MBPC-1 *Previous work by several groups has shown that various preexisting folds can be employed as stable scaffolds for hosting diverse metal coordination environments. Some of such engineered metalloproteins manifest properties characteristic of highly evolved natural systems, such as metal selectivity (30), redox tunability (31,32) as well as open coordination sites that allow for reactivity (33) and reversible small molecule binding (34). 1 These authors contributed equally to this work.…”
Section: Resultsmentioning
confidence: 99%
“…By removal of steric bulk above the plane of the Cys (replacing a Leu with an Ala, TRIL12AL16C), a cavity for a water molecule was achieved yielding a fully 4-coordinate CdS 3 O species (20). However, efforts to obtain 3-coordinate Cd(II) bound to Cys were unsuccessful (20,21).…”
mentioning
confidence: 99%
“…By removal of steric bulk above the plane of the Cys (replacing a Leu with an Ala, TRIL12AL16C), a cavity for a water molecule was achieved yielding a fully 4-coordinate CdS 3 O species (20). However, efforts to obtain 3-coordinate Cd(II) bound to Cys were unsuccessful (20,21). Ultimately, a pure CdS 3 environment was realized by resorting to the nonnatural amino acid analogue of Cys, penicillamine (Pen), in which bulky methyl groups replace the ␤-hydrogen atoms and are thought to exclude exogenous water from binding to the Cd(II).…”
mentioning
confidence: 99%
“…[4] In particular, we have asked whether the same metal can be bound to structurally related peptides with identical first-coordinationsphere ligands derived from the protein, but in one case form a trigonal structure and in a second case form a fourcoordinate pseudo-tetrahedral environment. [4] The relative importance of a metals geometric preference and the inherent protein structure is fundamental to understanding the folding, [5][6][7][8] stability, [9,10] and conformational changes [4,5,11] of metalloproteins, and hence the control of such site discrimination has been an important objective of protein design studies. The peptides described herein are variants of the TRI family of peptides shown in Table 1.…”
mentioning
confidence: 99%
“…The peptides described herein are variants of the TRI family of peptides shown in Table 1. The sequence of the TRI peptide is Ac-G(LKALEEK) 4 G-NH 2 . [12] A leucine residue at the hydrophobic layers is replaced by a cysteine residue at position 16 (TRI L16C) for generating a metal-binding site.…”
mentioning
confidence: 99%